The Influence of Collaborative Methods in English Language Learning on Student Empathy and Tolerance: Pengaruh Metode Kolaboratif Pembelajaran Bahasa Inggris pada Empati dan Toleransi Mahasiswa - Nuraeni, Rani; Natalia, Ester Ananda; Sihotang, Sondang Visiana; Aini, Qurotul; Rahardja, Untung (Pandawan Sejahtera Indonesia, 2025)
In the face of global challenges and increasing social polarization, empathy and tolerance have become essential components in shaping students’ character. Collaborative English language learning offers strong potential to foster these values through cross-perspective interaction. This study aims to explore the impact of collaborative learning methods in English language instruction on the development of students’ empathy and tolerance. This study aims to explore the impact of collaborative learning methods in English language instruction on the development of students’ empathy and tolerance. The approach centers on the implementation of collaborative techniques such as group discussions and perspective-sharing within English learning contexts. The learning process is designed to encourage active interaction and social reflection among students. Findings indicate that collaborative interaction enables students to appreciate diverse viewpoints, demonstrate mutual respect, and strengthen emotional and social awareness. Participatory learning activities help create an inclusive environment that supports character development. Collaborative English learning has proven effective in fostering empathy and tolerance among students. Therefore, integrating this approach into higher education curricula is a strategic step toward reinforcing character education that is responsive to multicultural society and global workforce demands.